EFFECT OF PROBIOTICS, PREBIOTICS AND SYNBIOTIC ON GROWTH PERFORMANCE OF BROILER UNDER DIFFERENT STOCK DENSITY - Aziz, H. I.; Al-Hawezy, D. J. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study was conducted to evaluate probiotic, prebiotic and synbiotic on the broiler growth performance, reread under different stock density. A total of 448 Ross 308 broiler reared for 6 weeks and divided into two groups normal density and high density . For each stock density birds were fed standard diet (T1), standard diet + 0.15g probiotic powder/ kg diet(T2), standard diet + 0.15g prebiotic powder/ kg diet(T3) and standard diet + 0.15g synbiotic powder/ kg diet (T4). All dietary additives had no significant differences (p≤ 0.01)on the body weight gain, feed intake and feed conversion ratio at 6 weeks of age. However, body weight was different significantly compared to the control group. Dietary synbiotic enhanced the body weight, body weight gain and feed conversion ratio. Broiler reared at high density had significantly affect body weight, body weight gains and feed intake. It was concluded that birds fed diet supplemented with synbiotic and reared at high density showed the highest (p≤ 0.01)body weight and body weight gain when compared with the other groups.